Optimalisasi Pembelajaran Pendidikan Agama Islam melalui Metode Blended Learning di MTs Al-I’anah Karawang - Adelia Pratiwi; Masykur H Mansyur; Neng Ulya (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
With the entry of the Covid-19 virus into Indonesia, the world of education must provide lots of new learning methods in order to achieve good learning goals. The COVID-19 pandemic has created a new challenge for the world of education in developing interesting and innovative learning quality so that distance learning continues as it should. With the help of technology as a learning medium, it makes it easier for students and educators to deal with learning problems during the pandemic. The use of appropriate Islamic religious education learning methods at uncertain times like this must be considered carefully by optimizing the use of blended learning methods. Blended learning is one of the methods that helps in distance learning faced during the pandemic with the intention of being able to adjust the situation in the form of distance or face-to-face after the pandemic ends. This study uses this type of research is a qualitative research conducted in the field. In data collection techniques using the method of observation, interviews, and researchers conducted data analysis through data reduction, data presentation, data levers and drawing conclusions. The results of this study indicate that the optimization of Islamic religious education learning with the blended learning method can achieve good learning objectives during the pandemic.